2012
DOI: 10.1177/1010539512460568
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Nonsmoking Policies and Tobacco Tax Increases

Abstract: Following the 2009 update of the 2005 Framework Convention on Tobacco Control, Vietnam issued a new policy to ban smoking at workplaces and public places. This cross-sectional survey explored public attitudes toward this new regulation and provides evidence to inform future laws. Using stratified cluster sampling, 10 383 Vietnamese people older than 15 years were drawn from 11 142 selected households. Policies mandating "no smoking at workplaces" were supported by 88.7% of Vietnamese adults, whereas "no smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
1
1
2
Order By: Relevance
“…This finding suggests a gap between attitude and practice of the poor against the violation of smoke-free regulations. On the contrary to the study finding by An et al [ 30 ], the poorer were less likely to support smoke-free policy. This difference could be explained by some hidden factors such as social norms as many scientists defined as “unwritten rules about behaviors” [ 5 , 33-36 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding suggests a gap between attitude and practice of the poor against the violation of smoke-free regulations. On the contrary to the study finding by An et al [ 30 ], the poorer were less likely to support smoke-free policy. This difference could be explained by some hidden factors such as social norms as many scientists defined as “unwritten rules about behaviors” [ 5 , 33-36 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, we found that people with lower economic status such as in the second and middle quintile were more likely to request smokers to stop smoking than those in the fourth and richest quintile. This result is not in concert with the study by An et al [ 30 ] showing that people with higher income demonstrated more positive attitudes towards “no smoking at workplaces” and at “public places”.…”
Section: Discussioncontrasting
confidence: 91%
“…Another explanation could be that women may feel more comfortable taking action in their own home and other familiar places, as opposed to public areas where they may not know the smoker. This result aligns with a previous study in Vietnam that found that only 69.8% of the population supported the ban on smoking in public places [44]. The law No.…”
Section: Discussionsupporting
confidence: 92%
“…Relatively few VHWs in this study were aware of the smoke-free policy; but awareness of this policy was associated with asking about tobacco use and advising smokers to quit. Suboptimal enforcement has led to inconsistent implementation of smoke free policy in CHCs (Dao et al, 2015), however, our findings suggest that raising awareness of this policy, alone, could have a positive impact on the provision of smoking cessation services.…”
Section: Discussionmentioning
confidence: 74%